Selection of Single-Visit and Multiple-Visit Root Canal Treatment Protocol: A Survey of Endodontic Specialists and General Dental Practioner of Pakistan (Medical Forum Monthly, 2024)
Objective: The aim of this study is to determine the selection and preference of single- and multi-visit root canal therapy by specialist’s endodontists and general dental practitioners of Pakistan and to inquire their motive for selecting the choice of treatment protocol in their practiceStudy Design: Comparative study.Place and Duration of Study: This study was conducted at the Department of Operative Dentistry and Oral Biology, Institute of Dentistry, LUMHS, Jamshoro from May 2016 to August 2016Material and Methods: A close ended questionnaire was send via emails, WhatsApp and Facebook accounts to 20 specialist endodontists and 150 selected GDPs in Pakistan to investigate their preference and motive for selecting the choice of treatment protocoleither single- or multi-visit for their patients. A literature search determined the commonest factors affect the choice of treatment either single- and multi-visit root canal treatment and were written in the questionnaire. The participants were informed to tick their response as agree, neutral and disagree as given in the questionnaire. The data collected were analyzed by the SPSS version 16. Frequency and percentages of variable like practice experience, current method of RCT and preference to the method of RCT were calculated. Chi-square tests were used to evaluate the differences in preference and current method of practice between both the groups of study. The level of statistical significance was set at 0.05.Results: Response rate was 100% in this study. Amongst all participants 29.4% have experience of less than 10 years and 70.6% have experience of more than 10 years. Generally all participants were practicing 72.4% multi-visit RCT and 27.6% single visit RCT. When both groups were compared by using chi-square test, GDPs preferred multiple-visit endodontic treatment and specialist Endodontist preferred single visit treatment. Also current method of performing root canal treatment by specialist endodontists is single visit procedure as compared to the GDPs, who performed mostly by multi-visit. Most important factor to be considered for multi-visit root canal treatment were outstanding effects of intracanalmedication, reduction of postoperative pain and easy collection of fees for multiple visit were 66.3%, 62.9% and 64.7% respectively.as compared to single visit root canal treatment, the most important factor considered were low risk and complication of local anesthetics 62.4 , treatment can be completed in one visit 52.4% , patient’s time limitation68.6%, dentist time limitation68.0% and patient preference 60.6%.Conclusion: In conclusion, most specialist endodontists perform and prefer single visit root canal treatment and GDPs preferred multi-visit root canal treatment.